COMPARATIVE ANALYSIS OF PRECAST HALF SLAB COST BUDGET PLANS WITH CONVENTIONAL CONCRETE PLATES - Hizballah, M Firoos; Suwandi, Putri Anggi Permata; Rizani, Mohammad Debby (Science and Technology Research Centre, Universitas PGRI Semarang, 2024)
The development of construction methods used in construction has progressed from year to year and in planning the construction of a building it is necessary to select several construction methods. Among them are casting methods that can be done conventionally in a more modern and practical way, namely by using precast. In this research, the floor slab construction method is planned using the conventional floor slab method and the precast half slab method in the Kajen Regional Hospital construction project. The purpose of this research is to analyze the cost efficiency and construction time between the conventional floor slab method and the precast half slab method. The results of the comparison analysis of the conventional floor slab method require a cost of Rp797,269,777.81 with an implementation time of 64 days while the precast half slab method requires a cost of Rp1,470,907,469.89 with an implementation time of 72 days.